2016
DOI: 10.1108/el-10-2014-0192
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of Web 2.0 by librarians in university libraries of East Azerbaijan, Iran

Abstract: Purpose-The present study aims to investigate levels of awareness and use of Web 2.0 tools by librarians in the university libraries of East Azerbaijan (EA) in Iran and to determine how librarians use these tools in everyday life. Design/methodology/approach-A Web-based questionnaire was used to collect data from 38 per cent librarians in the university libraries of EA. Findings-The research findings indicate that the librarians were more familiar with Web 2.0 tools such as wikis and blogs. While librarians wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Naturally, geography plays a role in countries like Iran who have officially banned the use of major social media platforms like Facebook and Twitter (Keown, 2020). In general, internet filtering, lack of access to high-speed internet and lack of training were the major obstacles for social media adoption by Iranian librarians (Ebrahimzadeh Pirshahid et al, 2016). In a similar study, Al-Kharousi et al ( 2016) identified both internal and external factors that affected the use of social media in Omani academic libraries.…”
Section: Factors Affecting Social Media Use Among Academicsmentioning
confidence: 99%
“…Naturally, geography plays a role in countries like Iran who have officially banned the use of major social media platforms like Facebook and Twitter (Keown, 2020). In general, internet filtering, lack of access to high-speed internet and lack of training were the major obstacles for social media adoption by Iranian librarians (Ebrahimzadeh Pirshahid et al, 2016). In a similar study, Al-Kharousi et al ( 2016) identified both internal and external factors that affected the use of social media in Omani academic libraries.…”
Section: Factors Affecting Social Media Use Among Academicsmentioning
confidence: 99%
“…Social media such as wikis and blogs has been adapted by librarians as online forum communication tools (Pirshahid, Naghshineh, & Fahimnia, 2016) to generate creative content, spreading information and getting feedback from users (Vucenovic, 2021). The widespread and diverse use of social media tools in libraries has a huge impact on social interactions among individuals, communities, and societies of all ages (Akeriwa et al, 2015), mainly among college and university students.…”
Section: Overview Of Social Media Use In Librariesmentioning
confidence: 99%